Joint design of mismatched filter and unimodular transmit waveform - Wang Tao; Chen Zihao; Cheng Zhiwei; Deng Xiaobo; Liang Junli; Bai Jianchao (Xibei Gongye Daxue Xuebao, 2021)
To improve the receiver performance, unimodular transmit waveform and mismatched filter are jointly designed by using the alternating direction method of multipliers (ADMM). A series of auxiliary variables are introduced to decouple the variables in objective function and additional constrains. Denominator normalization(fractional programming technology) and step function are applied to obtain optimal solution from some subproblems. For given transmit waveform, same-length mismatched filter is designed in receiver. The low sidelobe level performance of the present methods are illustrated with the simulation results.